A case of cardiac cyst hydatid with multiple system involvement - Mert Dogan, Gulec; Murat Dogan, Sait; Tasolar, Sevgi; Okut, Gokalp; Sigirci, Ahmet; Elkiran, Ozlem; Karakurt, Cemsit (Annals of Medical Research, 2021)
None